2008
DOI: 10.2353/ajpath.2008.080527
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Immunophilin FKBP52 Promotes Endometriosis

Abstract: Endometriosis is a common gynecological disease that affects approximately 10% of women of childbearing age. It is characterized by endometrial growth outside the uterus and often results in inflamed lesions, pain, and reduced fertility. Although heightened estrogenic activity and/or reduced progesterone responsiveness are considered to be involved in the etiology of endometriosis, neither the extent of their participation nor the underlying mechanisms are clearly understood. Heterogeneous uterine cell types d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 78 publications
(100 reference statements)
3
57
0
Order By: Relevance
“…This question was approached initially by confirming a report that FKBP4 mRNA levels are significantly lower in menstrual cycle-matched specimens of eutopic endometrium of women with endometriosis compared with endometriosis-free women (Hirota et al 2008) and extending these observations to include FKBP5. Subsequently, in vitro experiments evaluated the HOXA10, FKBP4, and FKBP5 mRNA and protein expressions and FKBP4 mRNA levels in the endometrium of women with and without endometriosis.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…This question was approached initially by confirming a report that FKBP4 mRNA levels are significantly lower in menstrual cycle-matched specimens of eutopic endometrium of women with endometriosis compared with endometriosis-free women (Hirota et al 2008) and extending these observations to include FKBP5. Subsequently, in vitro experiments evaluated the HOXA10, FKBP4, and FKBP5 mRNA and protein expressions and FKBP4 mRNA levels in the endometrium of women with and without endometriosis.…”
Section: Introductionmentioning
confidence: 54%
“…However, only implantation and decidualization are impaired in Fkbp4 knockout mice, indicating the selectivity and specificity of FKBP4 in mediating these progestin effects . Eutopic and ectopic endometria of women with endometriosis show significantly lower FKBP4 levels in both glands and stromal cells compared with women without endometriosis (Hirota et al 2008). Moreover, lower FKBP4 levels are reported in the endometria of baboons with experimentally induced endometriosis (Jackson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because our recent study has shown that FKBP52 levels are downregulated in endometria of women with endometriosis compared with women without endometriosis (29), reduced FKBP52 levels may lead to endometrial PRDX6 deficiency, increasing uterine susceptibility to ROS, aggravating endometriosis, and adversely affecting endometrial receptivity in patients with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR was performed as previously described (29). A housekeeping gene Gapdh was used as an internal standard.…”
Section: Methodsmentioning
confidence: 99%